Space, Mysticism, Romantic Music, Sequencing, and the Widening of Form in German "Krautrock" during the 70's - Einbrodt, Ulrich Dieter; Justus Liebig University Giessen (My University, 2001)
The examples show important elements of the whole range of German Krautrock in the seventies, from cosmic, electronic space musicover the romantic aspect to the fantasy style and to the sequencing pop of Kraftwerk. Many other Krautrock bands were popular and ofinfluence in the seventies. There is a new interest in England, and even modern techno and rave beats imitate structural Krautrock aspectsfrom electronic space music by relying on pulsating sequencer rhythms that have a lot in common with Tangerine Dream s space journeys,Faust s fuzzy repetitions or Kraftwerk s sequencing. This demonstrates that the innovative works of these German bands of the seventiesare - in retrospect - an important and influential part of rock history.
Keywords: ddc:780